Strategic Entrepreneurship, Business Model Agility, and Growth of Green SMEs in Indonesia: Adaptation to a Dynamic Business Environment - Siti Khusnul Rifani; Nina Fapari Arif; Fathi Habibatur Rahman (Journal of International Conference Proceedings, 2025)
This study examines the relationship between strategic entrepreneurship, business model agility, and the growth of green MSMEs in Indonesia, with an emphasis on the moderating role of adaptation to a dynamic business environment. This study was prompted by increasing global market volatility and the importance of sustainability-oriented business models for small and medium-sized enterprises. Using an explanatory quantitative design, data were collected from 287 green MSMEs in West Java, Yogyakarta, and East Java between April and August 2025 and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The results show that strategic entrepreneurship significantly enhances the growth of green SMEs, both directly and indirectly through business model agility, while adaptation to a dynamic environment strengthens these relationships. These findings highlight that entrepreneurial capability and agility serve as critical mechanisms for sustaining growth in uncertain markets. This study contributes to the integration of strategic entrepreneurship theory, dynamic capability theory, and contingency theory, with practical implications for SME leaders and policymakers to promote innovation, adaptability, and sustainable competitiveness.